Cytokeratins in hepatitis - YILMAZ, YUSUF (ELSEVIER SCIENCE BV, 2011)
Experimental and clinical evidence suggests that cytokeratins (CK), among other physiological functions, are expressed in hepatocytes and can be released in the bloodstream after acute or chronic inflammatory liver injury. Interest in CK in viral and nonviral hepatitis has been rapidly increasing during the last years, especially as they have been proposed as circulating biomarkers of hepatocyte necrosis and apoptosis. In the present review, we sought to summarize and discuss the alterations in circulating CK levels in different form viral and nonviral hepatitis, as well as their potential relation with liver histology. Understanding the mechanisms of hepatitis impact on CK and vice versa is a promising area of research that will positively enhance our understanding of the complexity of acute and chronic inflammatory liver injury. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hepatitis; Cytokeratins; Biomarkers; Liver biopsy; FATTY LIVER-DISEASE; C VIRUS-INFECTION; NORMAL AMINOTRANSFERASE LEVELS; POLYPEPTIDE-SPECIFIC ANTIGEN; APOPTOTIC CASPASE ACTIVITY; NONALCOHOLIC STEATOHEPATITIS; AUTOIMMUNE HEPATITIS; INTERMEDIATE-FILAMENTS; ALCOHOLIC HEPATITIS; SERUM-LEVELS